Left ventricular remodeling in patients with right ventricular myocardial infarction - M. T. Beyshenkulov; Z. M. Chazymova; A. S. Abylgazieva; K. R. Kaliev (Столичная издательская компания, 2015)
Aim. To study left ventricular (LV) remodeling, interventricular and intraventricular asynchrony in isolated inferior LV myocardial infarction (MI) or combined inferior LV MI with right ventricular (RV) MI. Material and methods. 57 patients with inferior LV MI with or without RV MI (n=57) were included in a 6-month prospective study. The patients were divided into 2 groups: Group 1 - patients with inferior LV MI (n=30); Group 2 - patients with inferior LV MI in combination with RV MI (n=27). Electrocardiography and echocardiography were performed in all patients at admission, on days 3, 30 and 180 after MI. Results. Significant signs of diastolic dysfunction (RV end-diastolic area 29.21±2.0 cm2) were found in group 2 on the third day after MI. A significant increase in the LV volume indices and diastolic sphericity index (from 0.54±0.02 to 0.59±0.03 units) and an increase in interventricular asynchrony (from 37.4±4.2 to 44.6±4.2 ms) were found in group 2 in 30 days after MI. Increasing tendency towards intraventricular and interventricular asynchrony, despite the absence of pathological LV remodeling, occurred in group 2 in 6  months after MI. Conclusion. Patients with RV MI have more pronounced maladaptive LV remodeling, intraventricular and interventricular asynchrony and greater LV diastolic dysfunction.